# Make an inductive conclusion about the nth term in following pattern, `1+2=(2*3)/2,1+2+3=(3*4)/2,1+2+3+4=(4*5)/2,...`

*print*Print*list*Cite

### 1 Answer

Given the following pattern:

`1+2=(2*3)/2,1+2+3=(3*4)/2,1+2+3+4=(4*5)/2,...`

Find an expression for the `n^(th)` term:

We are adding the natural numbers from 1 to `n` ; the sum is seen to be equal to the product of `n` and `n+1` all divided by 2.

------------------------------------------------------------------

**The inductive hypothesis is :**

`1+2+3+***+n=(n(n+1))/2` or `sum_1^n n=(n(n+1))/2`

------------------------------------------------------------------

This sums form a well-known sequence called the triangular numbers.

**Sources:**